Analytical approach and design method for evaluation of compressive arch action of precast concrete beams - Bao, Yintong (2023)
This paper proposes an analytical approach to predict compressive arch action (CAA) of precast reinforced concrete (PC) beams subjected to middle column removal scenario (MCRS). A beam-column joint with non-seismic detailing is employed in the prototype PC structures, which is a typical joint widely applied in low seismic-risk countries. However, under MCRS, a weaker sagging moment resistance of the precast interface near the removed middle column casts doubts on its structural performance. Based on particular details of the PC beams, the analytical approach is proposed to consider the influences of a potential plastic hinge at the PC interface, various precast interface locations, special precast reinforcing details and horizontal restraint conditions on the mobilisation of CAA. Furthermore, an easy-to-apply design method is developed by assuming linear relationships between bending moment, neutral axis depth and compression force of the PC beam. Reliability of the analytical approach and the design method is verified through comparisons between predictions and FEM simulations of typical two-span PC sub-assemblages with various design details. The comparison study suggests that both the analytical approach and design method can accurately predict the CAA capacity and corresponding displacement, as well as the maximum compression force and bending moment at PC beam ends. Finally, a parametric study is carried out to shed light on the effects of different precast interface locations and various common design details on CAA peak resistance. It is found that when the distance (L3) between the precast interface and the beam end interface does not exceed a threshold value (L3_c), increasing L3 can significantly enhance CAA capacity. However, when L3 exceeds L3_c, CAA cannot be further enhanced due to transformation of CAA mechanism. It also finds that the threshold value L3_c is highly influenced by reinforcement details, span-over-depth ratio and horizontal stiffness of the beam.